An Exploratory Study of Issues of EFL Learners in Pakistani University at Graduate Level - Tayyab, Javeria; Khawaja Hisham Ul Hassan; Akmal, Farhana (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims to address the challenges faced by English as a Foreign Language (EFL) learners at the graduate level in Pakistani universities. Despite the importance of English language in Pakistan, EFL learners face a range of issues that impact their language proficiency and academic success. This study is qualitative and uses thematic analysis to explore the experiences of EFL learners and identify the key issues that impact their language learning. The semi structured interviews have been taken from the EFL learners. The findings of this study have important implications for EFL instruction in Pakistani universities and can inform the development of targeted interventions to support EFL learners. The study highlights the significance of finding solutions to the issues faced by EFL learners in Pakistan, especially related to speaking skills, and offers recommendations for addressing these challenges.